Roleplay Method to Enhance Self-Protection Awareness Against Sexual Abuse in Children with Down Syndrome - Diah Daniswara Rahayu; Iim Wasliman (ITScience (Information Technology and Science), 2026)
Children with Down syndrome are at heightened risk of sexual abuse due to cognitive, communication, and social limitations, while self-protection education remains insufficiently integrated into special education practice. This study aims to examine the systematic implementation of the roleplay method in enhancing self-protection awareness against sexual abuse among children with Down syndrome. A qualitative case study design was employed in two special schools in Indonesia. Participants included students with Down syndrome, teachers, school principals, and parents. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that structured roleplay, implemented through careful planning, collaborative organization, guided simulation, and continuous evaluation, significantly improved students’ ability to recognize private body parts, differentiate between safe and unsafe touch, assertively refuse inappropriate behavior, and identify trusted adults to report to. Repetition and contextual variation of scenarios facilitated behavioral internalization and increased student confidence. The involvement of teachers, school leaders, and parents strengthened the intervention's sustainability and supported skill transfer beyond the classroom. This study contributes theoretically by integrating experiential learning principles with instructional management in special education contexts, and practically by offering a structured, replicable model for self-protection education. Roleplay emerges as an effective pedagogical strategy for promoting safety awareness and protective competencies among children with Down syndrome.